Zrównoważona karta wyników w internetowej sprzedaży bezpośredniej - Gabis, Elżbieta (Balanced scorecard in the internet direct sale, 2006)
Controllership faces new possibilities and challenges in the contemporary economy: modem technologies, development of the internet market, dynamism of its environment, globalization, increasing competition, fast rate of making decisions. Balanced Scorecard is an interesting tool of the strategic controllership worked out by Robert Kaplan and David Norton. The aim of this article is to present and evaluate this concept as well as the possibility of using it in e-business. Applying BSC in the internet direct sale can be helpful in estimating the efficiency of e-business actions and transition from the established goals to the actions causing the achievement of the planned value of measures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 121-127